2017
DOI: 10.3390/w9100743
|View full text |Cite
|
Sign up to set email alerts
|

Variation of Aridity Index and the Role of Climate Variables in the Southwest China

Abstract: Aridity index (AI), defined as the ratio of annual potential evapotranspiration to annual precipitation, has been widely applied in dividing climate regimes and monitoring drought events. Investigating variation of AI and the role of climate variables are thus of great significant for managing agricultural water resource and maintaining regional ecosystem stability. In this study, with the well-corrected precipitation records and the optimized parameters in estimating solar radiation, we investigated the varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…PET is influenced by several factors amongst which include net (solar) radiation, relative humidity, air temperatures, wind speed, atmospheric aerosol (including dust particles), type and size of vegetative cover, availability of soil moisture, reflective land surface, and change in land use/land cover [9][10][11]. Thus, any changes in these variables due to climate change are likely to change the value of PET that have a direct impact on precipitation and hydrological regimes as well as crop production through changes in the agro-ecological water balance [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…PET is influenced by several factors amongst which include net (solar) radiation, relative humidity, air temperatures, wind speed, atmospheric aerosol (including dust particles), type and size of vegetative cover, availability of soil moisture, reflective land surface, and change in land use/land cover [9][10][11]. Thus, any changes in these variables due to climate change are likely to change the value of PET that have a direct impact on precipitation and hydrological regimes as well as crop production through changes in the agro-ecological water balance [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the increasing AI in China will inevitably exert a significant effect on regional drought (Zhang et al, ; Zhang et al, ; Zhang et al, ). For example, in southwestern China, Li et al () found that the AI increased significantly during 1993–2015, and the drying atmosphere caused a strong autumn drought in 2009 (Zhang et al, ). This serious drought significantly reduced crop production and water supply and resulted in a lack of drinking water for more than 10 million people and economic losses of nearly $2.3 billion (Zhang et al, ; Sun et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, biases in precipitation data have been widely recognized due to station distribution, observational techniques and gauge measurement error (Goodison et al, ). Thus, applying corrections to remedy the measurement error in precipitation data is of great necessity before calculating the AI or other similar applications (Li et al, ). In China, Ye et al () studied the precipitation bias correction and found that wind‐induced gauge undercatch is the greatest measurement error in precipitation data in most regions, followed by wetting loss.…”
Section: Study Area and Data Usedmentioning
confidence: 99%
See 2 more Smart Citations